Building Tolerant Minds: Strategies for Integrating Religious Moderation in Schools - Nisa, Ike Hilatun; Rahmawati, Destiani; Komalasari, Dewi Tri (QuranicEdu: Journal of Islamic Education, 2025)
This study explores strategies for internalizing religious moderation within schools, recognized as crucial environments for student character development. Employing qualitative methods, including interviews and observations, the research reveals that fostering religious moderation enhances students’ appreciation of religious and cultural diversity. Key effective strategies identified include integrating religious moderation content into both the curriculum and extracurricular activities. The findings suggest that instilling values of religious moderation promotes tolerant, respectful attitudes among students. Moreover, balanced religious education contributes to shaping harmonious and well-rounded individuals capable of embracing diversity. The study concludes that the internalization of religious moderation should be implemented through systematic and targeted approaches to ensure students effectively apply these values in their daily lives, thereby supporting social cohesion and mutual respect in increasingly pluralistic societies.